Cancer Survivors' Perspectives of Virtual Yoga for Chronic Chemotherapy-Induced Peripheral Neuropathy Pain During the COVID-19 Pandemic. Issue 9 (4th September 2022) - Knoerl, Robert; Bockhoff, Julianna; Fox, Erica; Giobbie-Hurder, Anita; Berry, Donna L.; Berfield, Juliana; Meyerhardt, Jeffrey; Wright, Alexi; Ligibel, Jennifer
Abstract : With the rise in telehealth due to the COVID-19 pandemic, further research is needed to determine how to optimize virtual delivery of existing integrative oncology interventions for cancer treatment–related symptoms. The purpose of this qualitative analysis was to explore cancer survivors' perspectives of the acceptability and satisfaction of an 8-week, virtual yoga intervention for cancer survivors with chronic chemotherapy-induced peripheral neuropathy pain. Fourteen participants with chronic chemotherapy-induced peripheral neuropathy pain who completed the virtual yoga intervention were interviewed using a semistructured interview guide. Themes were derived from the data using inductive content analysis methods. Main findings from the interviews included the following: (1) participants were willing to try new nonpharmacological treatments for chemotherapy-induced peripheral neuropathy due to the high symptom burden and prior lack of success with medications; (2) participants highly rated the flexibility offered by the virtual format, but desired the social support potentially offered by practicing in-person yoga; and (3) the impact of virtual yoga on chemotherapy-induced peripheral neuropathy severity was unclear. There were several barriers to participants' use of virtual yoga for chronic chemotherapy-induced peripheral neuropathy pain (eg, technology, lack of space/equipment). The results may be used to improve the design and delivery of future trials testing virtual yoga for chronic chemotherapy-induced peripheral neuropathy pain.